Handwriting Character Recognition Javanese Letters Based on Artificial Neural Network - Ariyono Setiawan; Achmad Setya Prabowo; Eva Y Puspaningrum (IJCONSIST JOURNALS, 2019)
Abstract— Javanese character is one of Indonesia's cultural heritages that must be preserved. Manuscript form of the Javanese character is one of the priceless inheritances. Javanese characters are often called the Hanacaraka font. The development of technology especially in the field of image processing is one method to preserve the culture. The development of image processing methods for detecting characters from images with fewer errors is a great task. The purpose of this research is to create a system of Javanese character recognition from the handwriting into Latin character, so that the young generation can learn the form of Javanese character easily. The method used in this research is back-propagation as a classification method. The trial result of this recognition is to have accuracy 74 %.